Cellulase production by Scytalidium thermophilum and its potential use in rapid composting for Agaricus bisporus - Vijay, B; Sharma, Nitika; Kamal, Shwet (Mushroom Research, 2012)
Compost production is the most important and integral part of white button mushroom cultivation. It is a product of aerobic fermentation brought about by microbial successions, which starts with mesophiles, and later taken over by thermophiles. Thermophilic cellulases have the ability to operate at a higher temperature (>40Â°C) offering an advantage of increased reaction rate and suitable enzyme system for cellulose degradation. Moreover, the high operating temperature and acidic pH required by thermophilic fungi restrict the growth of contaminating organisms (Eriksen & Grksoyr, 1975; Romanelli et al., 1975; Rosenberg, 1975). During a survey, S. thermophilum (strain X-21) was invariably isolated form all the compost samples collected across the country. It was, therefore, thought prudent to screen this test strain for activity of extra cellular cellulolytic enzymes and its use to hasten the composting process. The influence of incubation time and temperature on the activity of cellulolytic enzymes of the test strain was also investigated during the study.